AL Ghazali’s View Regarding to the Witness in Islamic Wedding Ceremony - Jamaluddin Jamaluddin (Budapest International Research and Critics University, 2018)
One of the recognized and indisputable commandments of Islam is that of marriage - the sacred union that takes place only between a man and a woman. In relation to this revered bond, there are many verses of the noble Quran and countless a hadith that encourage marriage for any single man or woman - of any age or background. This is not only limited to the young brothers and sisters who have never been married and are looking for their life mate, but even those who have been through divorce have also been encouraged to re-marry and to